SISTEM INFORMASI INTERNSHIP MANAGEMENT APPLICATION SYSTEM (IMAS) BERBASIS WEB PADA PT. GMF AEROASIA CENGKARENG - Hani Dewi Ariessanti; Azizah Handayani Putri; Desy Indriyani (CCIT Journal, 2016)
The development of technology now has grown so rapidly, the Internet media has been widely used to obtain information, but data processing internship program at PT. Garuda Maintenance Facility AeroAsia still using semi-manual system. So that in the process of receiving and internship placement is still less efficient. The internship applying must wait for confirmation or receipt status for months. Because employees Learning Center Unit difficulty in finding a suitable placement with the majors and concentrations of the internship. On this issue, the authors conducted research internship program reception system in PT. Garuda Maintenance Facility AeroAsia order to provide quality of service information and up to date for potential applicants for internships. With the clarity of the status of applicants ease in carrying out the internship. Also allows employees of the company in the internship placement in each unit, it can also provide an assessment for the internship that have completed in accordance with the agreed time. Based on an idea that has been described above, implemented an idea that is poured on the journal titled "Information System of Internship Management Application System (IMAS) on PT. GMF Cengkareng."